Measurement, normalisation and mapping of urban-scale wind environment in Xi'an, China. Issue 9 (November 2019) - Zhang, Yunwei; He, Shan; Gu, Zhaolin; Wei, Na; Wah Yu, Chuck; Li, Xuxiang; Zhang, Renjian; Sun, Xian; Zhou, Dian
Studies on urban climatic mapping and local climate zones are urgently needed due to rapid urbanisation in China, to identify and predict serious air pollution problems and occurrence of urban heat islands, for sustainable urban planning. The study of wind environment, especially measurements of wind data on the urban scale, is important to the climate mapping and investigation of air pollution and heat island events. In this paper, we introduce a measurement method for the urban-scale wind environment, which combines measurements conducted at the stationary reference station with those at portable/mobile stations. Data collected from portable/mobile stations were normalised with respect to wind data measured at the stationary reference station. Three criteria for the selection of the stationary reference station were compared according to the land-use and distance to the portable/mobile stations. The background meteorological station was selected as the stationary reference station for data normalisation and was found to be the most appropriate. The normalisation method for wind data was used to analyse the measured wind data at portable/mobile stations. Clear differences were observed between measured and normalised average wind speeds. The normalised wind was used in the urban wind environment mapping. The objective of the mapping is to assess the ventilation potential of the urban canopy layer, to help the urban climate mapping and to inform future sustainable urban planning.